Recyclable montmorillonite-supported thiazolium ionic liquids for high-yielding and solvent-free upgrading of furfural and 5-hydroxymethylfurfural to C10 and C12 furoins. Issue 80 (12th August 2016) - Yan, Bing; Zang, Hongjun; Jiang, Yi; Yu, Songbai; Chen, Eugene Y.-X.
Abstract : Six Na + /montmorillonite (MMT) – supported thiazolium (TM) ionic liquids (ILs) have been synthesized and employed to catalyze the highly selective condensation of furfural (FF) and 5-hydroxymethylfurfural (HMF) into C10 and C12 furoins, respectively. Abstract : Six Na + /montmorillonite (MMT) – supported thiazolium (TM) ionic liquids (ILs), MMT–[TM], which are precatalysts to N-heterocyclic carbene (NHC) catalysts, have been synthesized and employed to catalyze the highly selective condensation of furfural (FF) and 5-hydroxymethylfurfural (HMF) into C10 and C12 furoins, respectively. Among them, five supported [TM] salts carrying the electron-donating group exhibit excellent catalytic activity. Thus, supported NHC catalysts, generated in situ from activation of MMT–[TM] with Et3 N, afford C10 and C12 furoins in 97–99% and 97–98% yield, respectively. This condensation reaction is also carried out under solvent-free conditions, and the catalysts can be readily recycled, showing no noticeable loss in their catalytic activity over four consecutive recycles. Thus, these desired features possessed by the current catalyst system have enabled the development of the greener and more environmentally benign process for the upgrading of FF and HMF.